2022
DOI: 10.3390/cancers14061384
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Tumour Heterogeneity: From Tissue to Liquid Biopsy

Abstract: Human solid malignancies harbour a heterogeneous set of cells with distinct genotypes and phenotypes. This heterogeneity is installed at multiple levels. A biological diversity is commonly observed between tumours from different patients (inter-tumour heterogeneity) and cannot be fully captured by the current consensus molecular classifications for specific cancers. To extend the complexity in cancer, there are substantial differences from cell to cell within an individual tumour (intra-tumour heterogeneity, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 160 publications
(190 reference statements)
0
39
0
1
Order By: Relevance
“…Although this model now appears to be both overly simplistic and fundamentally flawed, it did provide the basis for the development of rapid (e.g., 48 h incubation with a test drug), high throughput multiwell plate colorimetric (e.g., tetrazolium-based; crystal violet-based) and fluorometric (resazurin-based, such as CellTiter-Glo) assays for the assessment of cancer cell death post-treatment. These and other widely used preclinical assays (including colony forming ability, immunoblotting, flow cytometry, tumor growth delay in live animals) are not designed to recapitulate the degree of cellular and molecular complexity and heterogeneity that exists within a single tumor (intratumor heterogeneity) (reviewed in, e.g., [ 4 , 91 , 92 , 93 , 94 , 95 ]; also see Figure 2 B). Furthermore, continuous cell treatment with relatively high concentrations of chemotherapeutic drugs, which is required in order to induce a significant inhibitory effect (e.g., 50% “cytotoxicity”) in multiwell plate assays (see, e.g., [ 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 ]), often has little clinical relevance because many drugs are administered to a patient as a bolus [ 18 , 19 ].…”
Section: Snapshot Of the History Of Cancer Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this model now appears to be both overly simplistic and fundamentally flawed, it did provide the basis for the development of rapid (e.g., 48 h incubation with a test drug), high throughput multiwell plate colorimetric (e.g., tetrazolium-based; crystal violet-based) and fluorometric (resazurin-based, such as CellTiter-Glo) assays for the assessment of cancer cell death post-treatment. These and other widely used preclinical assays (including colony forming ability, immunoblotting, flow cytometry, tumor growth delay in live animals) are not designed to recapitulate the degree of cellular and molecular complexity and heterogeneity that exists within a single tumor (intratumor heterogeneity) (reviewed in, e.g., [ 4 , 91 , 92 , 93 , 94 , 95 ]; also see Figure 2 B). Furthermore, continuous cell treatment with relatively high concentrations of chemotherapeutic drugs, which is required in order to induce a significant inhibitory effect (e.g., 50% “cytotoxicity”) in multiwell plate assays (see, e.g., [ 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 ]), often has little clinical relevance because many drugs are administered to a patient as a bolus [ 18 , 19 ].…”
Section: Snapshot Of the History Of Cancer Researchmentioning
confidence: 99%
“… ( A ) Oversimplified (old) strategy for eradicating solid tumors through repeated doses of radiotherapy, chemotherapy, and other means (e.g., targeted therapies) when used singly or in various combinations; ( B ) Complex heterogeneity within an individual solid tumor (adapted from [ 91 ]). …”
Section: Figurementioning
confidence: 99%
“…In NSCLC, it was proved that the ctDNA genetic landscape is affected by the clonality of the primary tumor, as it may affect the metastatic process [ 97 ]. An NSCLC TRACERx study showed that the size of the primary tumor correlated with the higher number of clonal variants.…”
Section: Role Of Ctcs and Ctdna In Metastatic Spreadmentioning
confidence: 99%
“…27 Although novel research continues to evaluate the feasibility of computer algorithms to determine the optimal drug combinations while taking tumor heterogeneity into account, 72 others question the utility of liquid biopsy in sequencing tumor DNA from different metastasis and capturing tumor heterogeneity and charting clonal evolution during treatment. 73 An interesting observation seen in the companion to this article by Ambrosini et al 44 was that liquid biopsy in a patient detected an ALK resistance mutation that was not seen on lymph node NGS, and captured depletion of specific clonal populations during treatment.…”
mentioning
confidence: 94%